Insights into the effects of long-term biochar loading on water-soluble organic matter in soil: Implications for the vertical co-migration of heavy metals. (March 2020) - Fan, Qinya; Sun, Jianxiong; Quan, Guixiang; Yan, Jinlong; Gao, Jianhua; Zou, Xinqing; Cui, Liqiang
Highlights: Aromatics were dissolved out from biochar into WSOM and growing over biochar incorporation. EEM-spectra of WSOM was consisted of FA-like, tryptophan and HA-like compound. O-containing functional groups increased on biochar surface and enhanced complexation of WSOM. Cd concentration decreased but Pb increased in biochar-extracted WSOM. Abstract: Although interest in biochar remediation is growing, the effects of long-term biochar loading on soil environments have not been clearly confirmed. The contents and characteristics of water-soluble organic matter (WSOM) from soils after eight years of biochar remediation were investigated, and the vertical co-migration of heavy metals controlled by interactions between WSOM, soil and contaminants were also analyzed. The results showed that biochar-leaching WSOM featured high aromaticity. Fluorescence excitation–emission matrix (EEM) spectrophotometry was employed, and three primary components, including fulvic-acid-like (FA-like ), tryptophan, and humic-acid-like (HA-like ) compounds, were identified in the EEM spectra via parallel factor analysis models. With increasing biochar loading, FA-like and HA-like greatly increased, but tryptophan showed a weak response. Furthermore, the WSOM was freeze dried and analyzed with Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, and the results demonstrated that the BC treatment increased oxygen-containing functional groups and enhanced the complexation capability of the WSOM. Finally, the Cd and Pb concentrations in the WSOM were investigated, and Cd was found to decrease in top-soil WSOM with added BC because of increased complexation, but the Pb content increased because exchangeable and carbonate Pb converted into organic Pb. Further, the Cd and Pb concentrations decreased in sub-soil WSOM. These findings suggest that more efforts should be devoted to studying the effects of long-term biochar loading on soil environments.